A Learning Trajectory for Surface Area Concept with the Context of the Tourist Destination Bukit Sulap - Adha, Idul; Zulkardi; Putri, Ratu Ilma Indra; Somakim (Mathematics Education Journal, 2024)
The concept of surface area for flat shapes is often perceived as a challenging mathematical topic among elementary school students. In fact, the context of tourism can be integrated into the learning of geometry, for example, the topic of surface area. The objective of this study is to develop a learning trajectory that enhances problem-solving skills with respect to surface area problems in the context of Bukit Sulap, a tourism destination in Lubuklinggau City. The design research methodology, which included a validation study, was implemented in three stages: preparation and design, experimental teaching, and retrospective analysis. The subjects of this study were 27 elementary school students in Lubuklinggau City, Indonesia. The instruments utilized in this study included surface area problem solving task sheets, video recordings of in-depth interviews conducted during the learning process, field notes, and observation sheets. The findings of the study indicate that learning trajectories designed within the context of Bukit Sulap facilitate students' comprehension of problems, formulation of problem-solving strategies, implementation of these strategies, and interpretation of the results of problem-solving processes. The activities included in the learning trajectory are as follows: defining the contextual problem; self-review; designing a resolution plan; implementing the resolution plan; and establishing a mathematical model regarding surface area within the context used. Through the use of tourism as a context, students are expected to be able to solve surface area problems and learn the principles of surface area of flat shapes. This learning approach is an effective technique for improving problem-solving skills regarding surface area.